Community Empowerment In The Prevention And Management Of Hypertension - Marni, Marni; Firdaus, Insanul; Soares, Domingos; Mustain; Ananda Tri Nurjanah (Rajaki of Tulip Medika Publisher, 2025)
Background: Lack of public knowledge and awareness of healthy lifestyle habits to prevent hypertension. Purpose: community empowerment in helping and increasing community awareness and ability in treating hypertension. Methods FGD to form a hypertension care group. Education and Training of cadres and groups caring for hypertension, early detection, prevention, and management of hypertension. Developing a routine health check program, getting rid of cigarettes, exercising regularly, maintaining a balanced diet, getting enough rest, managing stress (CERDIK) as modified by the service team, and providing assistance to cadres or groups caring for hypertension in utilizing health facilities. Result: Restructuring of health cadres/hypertension care groups, cadre assistance has been implemented to conduct health checks, increased knowledge about prevention and management of hypertension, the knowledge score during the pre-test was 60 and after counseling the score increased to 85. Conclusion: restructuring and assistance and counseling for cadres to increase knowledge and increase motivation to actively help residents in living a healthy lifestyle so that they can prevent and overcome hypertension. Keywords: Community Empowerment, Management Of Hypertension, Prevention. Prevention